Thermal, environmental, and economic analysis of the gas turbine fogging system - Rash Sabah Aweid; Ahmed Nawfal Mustafa; Obed Majeed Ali; Bashar Mahmood Ali (Results in Engineering, 2025)
Ambient temperature can be considered a critical indicator of the efficiency and power production of gas turbines, especially in hot areas, so compressor air inlet cooling systems have been widely used to mitigate this problem. In this study, the performance of the fog system gas turbine power plant was analyzed, as actual operational data for the year 2023 was collected from the gas turbine power plant for two types of fuel used (crude oil and natural gas). ASPEN HYSYS V-10 was adopted to create analysis models with and without the fog system. The thermodynamic effects of integrating the fog system in a gas power plant indicated an improvement in some operating parameters, such as power production and thermal efficiency. The study results showed that the gas turbine's thermal efficiency increased by (10.7%) and (8.2%) for crude oil and natural gas fuel, respectively, with the fog system. It also turned out that the energy production from natural gas fuel using the fog system is the highest, reaching 112 MW compared to 102 MW for crude oil fuel; as for the specific fuel consumption, it decreased by 6.2% for natural gas, and by 5% for crude oil with the fog system, which indicates that the fog system in the gas turbine power plant is economically feasible in terms of fuel consumption, efficiency, energy requirements and greenhouse gas emissions.